(untitled) (Asian-Australasian Journal of Food Safety and Security, 2021)
The present study was aimed to detect and quantify major organophosphorus pesticide residues in cauliflower and cucumber collected from different retail markets of Dhaka city, Bangladesh. In this study, a total of 50 vegetable samples (30 samples of cauliflower and 20 samples of cucumber) were analyzed using Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and Gas Chromatography coupled with Flame Thermionic Detector (GC-FTD). Among the 30 analyzed samples of cauliflower, 5 samples (16.7% of the total number of samples) contained residues of chlorpyrifos, quinalphos, acephate and dimethoate, where 4 samples contained multiple pesticide residues. All the contaminated samples of cauliflower contained residues above the EU-MRL. On the other hand, among the 20 analyzed samples of cucumber, only 2 samples (10% of the total number of samples) contained residues of quinalphos and chlorpyrifos at a level being below the EU-MRL. This study reflects the overall scenario of pesticide residues remain in cauliflower and cucumber purchased from different local markets of Dhaka city, which will help the consumer to be aware of their health and safety. The findings derived from this study reveals the public health concern due to the potential of pesticide toxicity in vegetables for the consumers. Therefore, continuous monitoring on the use of pesticides in vegetables should be strengthened. Asian Australas. J. Food Saf. Secur. 2021, 5 (2), 63-70